A two-parameter approach to assessing notch fracture behaviour in clay/epoxy nanocomposites. (October 2015) - Hadj Meliani, M.; Azari, Z.; Al-Qadhi, M.; Merah, N.; Pluvinage, G.
Abstract: Fracture toughness and other mechanical properties of epoxy are known to be affected by the addition of nanoclays. Fracture toughness has been shown by many researchers to depend on the nanocomposite structure with well-dispersed and distributed nanoparticles resulting in improvements in this property by up to 50%. Notch fracture toughness depends on the acuity of the notch as well as on the structure of the nanocomposite. In the present work, a two-parameter fracture criterion based on a critical notch stress intensity factor, Kρ, c, and effective T-stress, Tef, was used to study the effect of notch severity and nanoclay addition on the fracture toughness of the epoxy matrix. The results show that the average value of K ρ, c for neat epoxy increased with increasing notch radius while the absolute value of Tef decreased with notch radius. The addition of nanoclay to pristine epoxy reduced the average value of K ρ, c and increased the absolute value of Tef . The critical notch radius was found to be around 1.0 mm and the notch sensitivity was higher for neat epoxy. SEM analysis of the fractured surfaces revealed that the lower K ρ, c for nanocomposites in both mode I and mixed mode fractures was due to early crack initiation at clay clusters or voids at the notch root.